Comparing tree swallow dispersal strategies in a continuous mainland environment - Kelly K. Hallinger; Teresa M. Pegan; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; David Chang van Oordt; Valentina Ferretti; Anna M. Forsman; Jennifer R. Gaul; Paulo E. Llambías; Sophia C. Orzechowski; J. Ryan Shipley; et al. (Ecology, 2026)
Dispersal is one of the most important aspects of animal behavior and can have far‐reaching consequences for organismal ecology and evolution. Despite recent theoretical advances in understanding why individuals within the same population vary in dispersal behavior, relatively few studies have empirically evaluated the long‐term causes and consequences of variable dispersal within natural populations. In this study, we used life history data collected over the course of 16 years to examine fitness outcomes in 867 known‐age female tree swallows breeding in New York, USA, that differed in their dispersal status: “immigrant” females, defined as dispersers that hatched elsewhere, and “local” females, defined as non‐dispersers that hatched within the study site and returned there after migration to breed. We also compared the life history responses of immigrant and local females to natural variation in weather, nest predation risk, and social environment at their breeding site. Local females were more likely to produce fledglings that recruited into the study area as adults. We also found several instances in which dispersal status interacted with an environmental metric to influence relative fitness, and these responses were largely consistent across life history measures. Overall, immigrant females were relatively resilient to variation in their extrinsic environment, while local females were highly sensitive to environmental conditions at the breeding site, performing relatively well when conditions were benign and faring relatively poorly as conditions became more stressful. We found little evidence that distance dispersed within a study site impacted female fitness, suggesting that the dispersal‐associated differences in fitness that we observed operate mostly across broader spatial scales. Future work should undertake the direct and simultaneous measurement of behavior, physiology, and fitness of immigrant and local females across environmental contexts and should seek to understand whether and how context‐dependent fitness variation of dispersers and non‐dispersers scales up to influence larger ecological and evolutionary processes.

Full lifetime perspectives on the costs and benefits of lay‐date variation in tree swallows - David W. Winkler; Kelly K. Hallinger; Teresa M. Pegan; Conor C. Taff; Mo A. Verhoeven; David Chang van Oordt; Maria Stager; Jennifer J. Uehling; Maren N. Vitousek; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; et al. (Ecology, 2020)
Animals must balance various costs and benefits when deciding when to breed. The costs and benefits of breeding at different times have received much attention, but most studies have been limited to investigating short‐term season‐to‐season fitness effects. However, breeding early, versus late, in a season may influence lifetime fitness over many years, trading off in complex ways across the breeder’s lifespan. In this study, we examined the complete life histories of 867 female tree swallows ( Tachycineta bicolor ) breeding in Ithaca, New York, between 2002 and 2016. Earlier breeders outperformed later breeders in short‐term measures of reproductive output and offspring quality. Though there were weak indications that females paid long‐term future survival costs for breeding early, lifetime fledgling output was markedly higher overall in early‐breeding birds. Importantly, older females breeding later in the season did not experience compensating life history advantages that suggested an alternative equal‐fitness breeding strategy. Rather, most or all of the swallows appear to be breeding as early as they can, and differences in lay dates appear to be determined primarily by differences in individual quality or condition. Lay date had a significant repeatability across breeding attempts by the same female, and the first lay date of females fledged in our population was strongly influenced by the first lay date of their mothers, indicating the potential for ongoing selection on lay date. By examining performance over the entire lifespan of a large number of individuals, we were able to clarify the relationship between timing of breeding and fitness and gain new insight into the sources of variability in this important life history trait.